NEW POSSIBILITIES OF CORRECTION OF CLINICAL STATUS AND ENDOTHELIAL DYSFUNCTION IN CORONARY HEART DISEASE PATIENTS - Kuzminova, N.V.; Romanova, V.О.; Serkova, V.K.; Belovol, О.М.; Knyazkova, І.І.; Gavriluk, А.О. (World of Medicine and Biology, 2019)
112 patients with coronary heart disease (CHD) were examined: 76 of them were diagnosed with stable CHD, 36 patients were hospitalized with acute coronary syndrome. To assess the effectiveness of treatment, patients were divided into two groups. The first group (n=69) received complex basic therapy of coronary heart disease. Patients of the second group (n=43) additionally to basic therapy received a fixed combination of meldonium (180 mg) with gamma-butyrobetaine (60 mg) orally 2 capsules twice daily during 4 weeks. Complex therapy of CHD patients with the combination of meldonium and gamma-butyrobetaine (was evaluated 1 month after start) contributed to a significant (p
Keywords: coronary heart disease; endothelial dysfunction; meldonium; gamma-butyrobetaine